Analisis Kinerja Keuangan Perbankan dengan Menggunakan Metode Camel (Studi Kasus pada PT. BPR Buduran Delta Purnama) - Wisnu P Setiyono; Miftakhul Nur Aini (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2014)
Based on the provisions of The Central Bank, All Indonesian banking institutions are obliged to report their performance to the financial services authority (FSA) and always adhere to the provisions of the law prevailing in the region of Indonesia. Therefore, all banking institutions will be assessed its performance by using CAMEL methods, including capital, assets, management, earnings and liquidity. By using a descriptive quantitative research method, this research employes 5 (five) aspects of banking assessment, for instance; capital ratios, we use CAR (Capital Adequacy Ratio); earning ratios and assets quality, we employes KAP (earning assets) and PPAP (Allowance for Earning Assets); Special for management aspects we apply a survey to the general management and risk management officer; from the aspect of profitability, we utilise ROA (Return On Assets ratios) and ROA (Operating Expenses to Operating Income ratios); finally, the aspect of liquidity ratios, we use Cash Ratios and LDR (Loan to Deposit Ratios). The result of 3 (three) years (2011 to 2013) assessments, we found that The BPR Buduran Delta Purnama has good banking performance (credit score more than 81 which the minimum score for good or bad banking performance). It is based on some benchmarks to determine the reliability of the bank after the assessment of each variable. We used a primary data obtained through questionnaires and secondary data in the form of financial statements balance sheet and income statement of PT. BPR Buduran Delta Purnama between 2011 to 2013.